Emulsion droplet crystallinity attenuates early in vitro digestive lipolysis and beta-carotene bioaccessibility. (15th September 2018) - Hart, Samantha M.; Lin, Xinjie (Lois); Thilakarathna, Surangi H.; Wright, Amanda J.
Highlights: Compositionally equivalent liquid versus solid cocoa butter emulsion droplets were produced. Particle size, shape, charge, melting, and polymorphism were similar with BC. Degradation of encapsulated BC was similar between solid and liquid droplets. Early in vitro digestive lipolysis and BC bioaccessibility were higher for the liquid droplets. Abstract: The impacts of lipid crystallinity on in vitro digestive lipolysis and bioaccessibility of encapsulated (0.1 wt%) beta-carotene (BC) were investigated for a 15 wt% cocoa butter emulsion prepared as crystalline (i.e. solid emulsions, SE & SE-BC) or undercooled (liquid emulsions, LE & LE-BC) droplets at 25 °C. Particle size distributions (D4, 3 ∼0.7 μm), morphology (spherical), polymorphism (beta-V), thermal behavior (peak melting ∼30 °C), zeta potential (∼−44 mV) and BC degradation under accelerated lighting conditions were similarly extensive. Following exposure to simulated gastric conditions, duodenal hydrolysis and BC bioaccessibility were lower for SE-BC up to 2 h (P < 0.05). Ultimately, samples with both solid and liquid droplets were hydrolyzed extensively and BC bioaccessibility did not differ (P > 0.05). Therefore, for compositionally equivalent emulsions, lipid droplet solid state delayed digestive lipolysis and bioactive solubilization. These results help to clarify the role of lipid physical state on dietary lipid digestion and bioactive release.